1998
DOI: 10.1007/s002560050354
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastic osteosarcoma: characterisation by gadolinium-enhanced MR imaging correlated with histopathology

Abstract: Gd-enhanced MR imaging can assist in obtaining diagnostic biopsy material of chondroblastic osteosarcoma by identifying both osteoid- and chondroid-forming areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, in spite of recent improvements in MRI (20), the histological diagnosis of bone tumors by MRI is still difficult. Geirnaerdt et al (17) demonstrated that septonodular and peripheral rim enhancement observed on Gd-enhanced MR images supported the diagnosis of a chondroblastic osteosarcoma. However, our results demonstrate that septonodular and peripheral rim enhancement patterns are characteristic patterns for chondroid matrix-forming tumors (21,22), not exclusively for chondroblastic osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in spite of recent improvements in MRI (20), the histological diagnosis of bone tumors by MRI is still difficult. Geirnaerdt et al (17) demonstrated that septonodular and peripheral rim enhancement observed on Gd-enhanced MR images supported the diagnosis of a chondroblastic osteosarcoma. However, our results demonstrate that septonodular and peripheral rim enhancement patterns are characteristic patterns for chondroid matrix-forming tumors (21,22), not exclusively for chondroblastic osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…For the Gd-enhanced MR images, the classification of the enhancement pattern described by Geirnaerdt et al (17), as (a) none, (b) septonodular, when curvilinear lines and nodules were observed within an otherwise nonenhancing areas, (c) heterogeneous, or (d) rim, when an enhancing peripheral rim of variable thickness was seen. These patterns were not mutually exclusive in one tumor.…”
Section: Image Analysismentioning
confidence: 99%
“…There are also results to suggest that the use of contrast medium may contribute to the accuracy of bone lesion detection in MRI. This is the case especially in recurrent malignancies and in certain types of cartilaginous lesions [19]; however, we did not find any advantage in lesion visualization when contrast was used. It is to be noted that our data did not include any primary malignant bone or cartilaginous tumors.…”
Section: Discussionmentioning
confidence: 82%
“…The MRI has a better sensitivity and tissue contrast than CT. For example, oedematous lesions in bone can often be visualized only in MRI as a bright involvement of bone marrow in a heavily T2-weighted and short tau inversion recovery (STIR) sequences [8,10]. Contrast medium provides more accuracy in detecting viable parts in, for example, recurrent malignancies and certain types of cartilaginous lesions [31]. Parkkola et al [32] showed that, with dynamic contrast-enhanced MRI, biopsies can be taken from the vital part of the tumour avoiding the necrotic areas.…”
Section: Discussionmentioning
confidence: 98%